What are the individual characteristics or skills associated with baseball batting performance? A scoping review - Tremblay, M.; Couëpel, B.; Abboud, J.; Descarreaux, M. (Sports Medicine - Open, 2025)
Background In baseball, batting performance can be measured using game and advanced statistics as well as hitting metrics. To date, the core set of individual characteristics or skills associated with superior batting performance remains to be identified. The aim of this scoping review was to identify and classify the individual characteristics or skills associated with baseball batting performance indicators and describe the methods used to assess these individual characteristics or skills and batting performance indicators.